Lamb production of prolific sheep - Ismeth Inounu; Bess Tiesnamurti; Subandriyo .; Harimurti Martojo (Jurnal Ilmu Ternak dan Veteriner, 1999)
The research was aimed to study factors that affected litter size (JAS), lamb survival (DHA) and litter weight at birth (BL) and at weaning (BS) on prolific ewes. Production records during the year of 1981-1993 were used in this study (1,437 records). Ewe genotypes (G), management levels (M), ewe parity (P) were the fixed effect and ewe gestation gain (PKB) was a covariable that included in the model. Analysis of variance for unbalanced data with general linear model procedure were used. Mean JAS was 1.77. Sources of variation that affected JAS were G, M, P-M interaction, and PKB. One copy of FecF gene increased the number of lambs born by 0.8. Changing toward a better management levels was followed by an increase of JAS. An increased of one kilogram PKB was also followed by an increase of 0.04 litter size born. The mean of BL was 3.43 kg and the sources of variation that affected BL were G, M and P-M interaction. At all management levels, primipara ewes had lower litter size at birth and litter birth weight than the pluripara ewes. Mean DHA found was 73.93%, it was affected by G-M interaction, P and PKB. First parity ewes has 11% lower of DHA than second parity ewes. An increase of 1 kg PKB was followed by an increase of 2.3% of DHA. Sources of variation that affected BS were G-M interaction, P and PKB. Mean BS in this study was 13.12 kg.   Key words : Prolific sheep, lamb production